Intercultural communication through social media and its impact on tourism industry. (11th June 2021) - Das, Jyoti Ranjan; Panigrahi, Rashmi Ranjan; Khatua, Ajay Ku.
Intercultural communication (IC) through social media plays a vital role in the growth and development of tourism industry. In today's scenario intercultural communication via social media plays a pivotal role in tour and travel decisions. Social media (SM) has been considered as the most accepted platform for exchanging of information. This article is based on the objective to know the contribution of social media on the growth of Indian tour and travel industry. Data are collected from primary sources through structured questionnaire from respondents of four selected states of India, i.e., Odisha, Bihar, Chhattisgarh and West Bengal and analysed with the help of descriptive statistics. This research identifies the positive contribution of intercultural communication with development of tourism sector with the help of social media platform. Research contributes for the development of tourism industry and also helpful in tour and travel decision.